KEPEMIMPINAN DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Suryadi '; M.Y. Tiyas Tinov (Jurnal Kebijakan Publik, 2013)
The purpose of this study isto investigate and analyze the influence of principal leadership on student achievement at SMANegeri 1 Benai Singingi Kuantan District. This study was conducted at SMA Negeri 1 BenaiSingingi Kuantan District, where the population and the sample is the school committee, board ofeducation, teachers, school staff, parents and pupils. The data was collected by distributingquestionnaires and observation techniques, once the data is collected and then analyzed usingquantitative descriptive analysis. The result showed that the leadership of the principal SMANegeri 1 Benai was pretty good and held student achievement is quite good as well. While theinfluence exerted by the variable X (the leadership of principal) to variable Y (student achievement)is quite strong.